EFEKTIVITAS PROSES PEMBUATAN DOKUMEN PEMBERITAHUAN IMPOR BARANG DAN PENGAMBILAN BARANG PADA PT.PALEM TAMA SAMUDRA - Qodri Setiawan; Rousdy Safari Tamba; Sukirno Sukirno (JAMBIS : Jurnal Administrasi Bisnis, 2022)
In Indonesia to import goods must meet various procedures and regulations in accordance with the regulations of the Directorate General of Customs and excise under the regulation of the Minister of Finance and the applicable laws so as not to cause harm to the country. Documents required in the process of importation of goods is a document notification of import of goods. The definition of a notice of import of goods itself is a notification document on the import of goods by the importer to Customs and excise based on complementary customs documents in accordance with the principle of self assessment. This study aims to analyze the effectiveness of the process of making import notification documents and analyze the constraints in the process of making import documents , as well as to analyze the solution to these problems at PT. Tama Samudra Palm. The research method used is descriptive qualitative . The results of research on the effectiveness of the process of making PIB documents and taking goods at PT. palem Tama Samudra there are 3 indicators, namely the utilization of human resources, facilities and infrastructure. In the utilization of human resources is considered less effective or close to effective because there are still some obstacles in the implementation of procedures for making PIB documents, while the facilities and infrastructure are already effective